2015
DOI: 10.1111/nph.13784
|View full text |Cite
|
Sign up to set email alerts
|

Massive intracellular gene transfer during plastid genome reduction in nongreen Orobanchaceae

Abstract: SummaryPlastid genomes (plastomes) of nonphotosynthetic plants experience extensive gene losses and an acceleration of molecular evolutionary rates. Here, we inferred the mechanisms and timing of reductive genome evolution under relaxed selection in the broomrape family (Orobanchaceae).We analyzed the plastomes of several parasites with a major focus on the genus Orobanche using genome-descriptive and Bayesian phylogenetic-comparative methods. Besides this, we scanned the parasites' other cellular genomes to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 77 publications
4
97
1
1
Order By: Relevance
“…We compared nonsynonymous (dN) and synonymous (dS) nucleotide substitution rates of all Orobanchaceae with closely related nonparasites ( Fig. 1), building on phylogenetic relationships established earlier (10,11). In gene-by-gene likelihood ratio tests (LRTs), the facultatively hemiparasitic Triphysaria versicolor shows hardly any significant rate shifts in plastid genes compared with nonparasitic plants (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We compared nonsynonymous (dN) and synonymous (dS) nucleotide substitution rates of all Orobanchaceae with closely related nonparasites ( Fig. 1), building on phylogenetic relationships established earlier (10,11). In gene-by-gene likelihood ratio tests (LRTs), the facultatively hemiparasitic Triphysaria versicolor shows hardly any significant rate shifts in plastid genes compared with nonparasitic plants (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This first phase of selection relaxation is characterized by a steady increase of microstructural changes and the acceleration of dN and dS. Following this episode of selectional shift, evolutionary rates in the plastome evolve at a new equilibrium, perhaps matching the modified transcript and protein requirements (11). This molecular evolutionary regime shift is repeated once selective constraints on plastid proteins (e.g., ATP synthase) that continue to function for a longer period are lost or functionally replaced (functional loss 3 in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective pressure leads to divergent traits during plant evolution, which may be tracked in chloroplast genomes, for instance, the non-photosynthetic lifestyle of certain plant groups such as Epipogium aphyllum and Epipogium roseum [5], Orobanche [13], and Petrosavia stellaris [55] tends to be associated with the enormously reduced cp genome size. Complete sequencing and comparative analyses here revealed that the Clematoclethra species ( C .…”
Section: Discussionmentioning
confidence: 99%
“…orchids [8], Campanulaceae [9] and Rafflesiaceae [10]. Additionally, gene transfer between plastome, chondrome and nucleus has also been revealed in plants [1113]. It has been proven that cp genome structural variations are accompanied by speciation over time, which likely provides evolutionary information [14].…”
Section: Introductionmentioning
confidence: 99%